How to manage transgenerational entrepreneurship : an analysis within family businesses. - Matthias Alfred Tietz. (2010)
This thesis examines the question of how to manage transgenerational entrepreneurship within the family business. It sets out to facilitate a better understanding of family businesses and transgenerational entrepreneurship so that the thousands of family businesses, whose transitions affect many jobs each year, continue to be the backbone of our economies.